2015
DOI: 10.3390/beverages1020034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fresh and Commercial Pomegranate Juices from Mollar de Elche Cultivar Grown under Conventional or Organic Farming Practices

Abstract: Abstract:Pomegranate juice has gained a high reputation for its health properties and consequently is now a highly demanded product. However, there is an interest in knowing if there are differences between conventional and organic agricultural practices. For that reason, total phenolic content, antioxidant capacity, punicalagin isomers and sensory analysis of pomegranate juices from Mollar de Elche cultivar were studied. A comparison between fresh and commercial pomegranate juice obtained by conventional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 28 publications
4
15
0
Order By: Relevance
“…No significant differences of TPC values were found in organic and conventional commercial Pom juice when investigated by Nuncio‐Jáuregui et al. ().…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…No significant differences of TPC values were found in organic and conventional commercial Pom juice when investigated by Nuncio‐Jáuregui et al. ().…”
Section: Resultsmentioning
confidence: 89%
“…() observed that the Pn content in organic Pom Spanish juices was approximately half the content of the conventional juices, presenting 0.10 and 0.20 mg/mL, respectively. Additionally, Nuncio‐Jáuregui, Cano‐Lamadrid, Hernández, Carbonell‐Barrachina, and Calín‐Sánchez () also reported conventional juices having higher Pn content than organic ones. Although differences in the content of biologically active compounds have been reported among organic and conventional juices, no relationship can be established with farming practices given that ellagitannin content depends on the combination of cultivar and climate conditions, variety, processing methods, and research techniques (Bunea et al., ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Significant process losses for TPC (and antioxidant capacity) were reported also when manufacturing pomegranate nectar from whole fruit [14]; under such circumstances, about 37% TPC was associated with pasteurized PJ compared with 47% associated with peel [14]. There were no TPC differences were reported for PJ extracted using organically grown versus conventionally grown pomegranate fruits [28].…”
Section: Total Antioxidant Capacity and Tpc Of Pomegranate Juicementioning
confidence: 96%
“…The observed total antioxidant capacity and TPC values are for unpeeled whole fruit, and values might also be moderated by drying and the efficiency of the extraction. In other studies, juice is extracted from fresh whole pomegranates, or fruits were homogenized or macerated directly with solvent, and the extract subjected to analysis; typically, such data were then adjusted for moisture content [14,[26][27][28][29][30][31]. There has been no concerted investigation to examine whether analysis of fresh or dried sample extracts (two alternative sample treatment regimens) affect the final results materially.…”
Section: Total Antioxidant Capacity and Tpc For Pomegranate Fruitmentioning
confidence: 99%